Electrical safety in low voltage distribution systems up to 1000 V a.c. and 1500 V d.c. Equipment for testing, measuring ormonitoring of protective measures. Equipment for insulation fault location in IT systems Part 9, (15th October 2000) - British Standards Institution,
No abstract available